2011
DOI: 10.1371/journal.pone.0020144
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Anthropogenic Landscape Features on Population Genetic Differentiation of Przewalski's Gazelle: Main Role of Human Settlement

Abstract: Anthropogenic landscapes influence evolutionary processes such as population genetic differentiation, however, not every type of landscape features exert the same effect on a species, hence it is necessary to estimate their relative effect for species management and conservation. Przewalski's gazelle (Procapra przewalskii), which inhabits a human-altered area on Qinghai-Tibet Plateau, is one of the most endangered antelope species in the world. Here, we report a landscape genetic study on Przewalski's gazelle.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 65 publications
2
34
0
1
Order By: Relevance
“…The remained populations of the Przewalskii gazelle in Qinghai Lake region are much closer to P. p. diversicornis; they do show minor variation in horn shape other skull structures, and the distribution patterns of the local populations are largely in accordance with the observed pattern of genetic differentiation [30]. The exception is the Wayu population, which is fully distinct (100%) from all other populations of the species.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…The remained populations of the Przewalskii gazelle in Qinghai Lake region are much closer to P. p. diversicornis; they do show minor variation in horn shape other skull structures, and the distribution patterns of the local populations are largely in accordance with the observed pattern of genetic differentiation [30]. The exception is the Wayu population, which is fully distinct (100%) from all other populations of the species.…”
Section: Discussionsupporting
confidence: 58%
“…The species is still threatened, however, because both the human population and domestic livestock are increasing and the habitat are further fragmented around Qinghai Lake. Furthermore, the gene flows in the isolated populations of Przewalski's gazelle are very limited [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We never found individuals that moved from Hudong-Ketu to Yuanzhe area during our field tracking surveys and our results show that habitat area of the local populations were clearly reduced after the grassland was fenced in the early 1990s (Figure 3). Recent reports on the genetic structure of the Przewalski's gazelle also indicated the anthropogenic landscape had deeper impacts on the population structure than lake and mountains [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Reh and Seitz (1990), using a sample design that included several sites and enzyme analyses, found that railways contributed to the isolation, and thus the inbreeding, of common frogs (Rana temporaria) in Germany. Yang et al (2011) used landscape analysis and genetics based on microsatellites to identify the factors influencing the differentiation among Przewalski's gazelle (P. przewalskii) populations in China. Prunier et al (2014) used a microsatellite individual-based sampling scheme combined with computer simulations to determine whether HSR in west-central France was old enough to cause genetic discontinuities in the alpine newt (Ichthyosaura alpestris).…”
Section: Indirect Methodsmentioning
confidence: 99%